Secrets not meant to be kept - Miklowitz, Gloria D. (New York Delacorte Press, 1987)
Her three-year-old sister's changing behavior unleashes many long-surpressed disturbing memories from Adrienne's own days at a highly respected local preschool.
Keywords: Child sexual abuse -- Fiction